An integrated dynamic voltage control strategy in active distribution network based on improved model predictive control. Issue 5 (13th April 2022) - Li, Yize; Wang, Yinfeng; Ye, Hongbo; Xie, Wei; Hua, Bin; Lu, Chao
Abstract: The distribution networks have more frequent and fast voltage fluctuations with the large‐scale access of distributed energy resources and electric vehicles. Based on remote terminal unit (RTU) and distribution terminal unit (DTU), traditional hierarchical control methods are difficult to achieve rapid global coordinated voltage regulation due to static modeling. For this purpose, this paper proposes an integrated dynamic voltage control strategy which integrates the objectives of local voltage control and secondary voltage control. First, simplified dynamic models of controllable equipment in active distribution network are established instead of the static models. On this basis, the state‐space prediction model of the control system is established. Then, based on the improved model predictive control (IMPC), the integrated dynamic voltage control strategy realizes rapid and global coordinated control through state prediction, rolling optimization and real‐time feedback correction. Numerical results show that the proposed strategy can achieve fast global coordinated voltage control in the time scale of seconds.